Current biomarkers of canine mammary tumors - Kaszak, Ilona; Ruszczak, Anna; Kanafa, Szymon; Kacprzak, Kamil; Król, Magdalena; Jurka, Piotr (Acta veterinaria scandinavica, 2018)
Mammary tumors are the second most common neoplasia in dogs. Due to the high similarity of canine mammary tumors (CMT) to human breast cancers (HBC), human biomarkers of HBC are also detectable in cases of CMT. The evaluation of biomarkers enables clinical diagnoses, treatment options and prognosis for bitches suffering from this disease. The aim of this article is to give a short summary of the biomarkers of CMT based on current literature. Very promising biomarkers are miRNAs, cancer stem cells, and circulating tumor cells, as well as mutations of the breast cancer 1 gene (BRCA1) and breast cancer 2 gene (BRCA2). Until now, the most studied and reliable biomarkers of CMT have remained antigen Ki-67 (Ki-67), endothelial growth factor receptor, human epidermal growth factor receptor 2 (HER-2), estrogen receptor, progesterone receptor and cyclooxygenase 1 (COX-2), which can be detected in both serum and tissue samples using different molecular methods. However, carcinoembryonic antigen and cancer antigen 15-3 (CA 15-3), while poorly studied, seem to be good biomarkers, especially for the early detection and prognosis of CMT. We will also mention the following: proliferative cell nuclear antigen, tumor protein p53 (p53), E-cadherin, vascular endothelial growth factor, microRNAs, cancer stem cells and circulating tumor cells, which can also be useful biomarkers. Although many studies have been conducted so far, the estimation of biomarkers in cases of CMT is still not a common practice, and more detailed research should be done.